2013
DOI: 10.1016/j.molcel.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Human Base Excision Repair Enzyme SMUG1 Directly Interacts with DKC1 and Contributes to RNA Quality Control

Abstract: Single-strand-selective monofunctional uracil-DNA glycosylase 1 (SMUG1) is a base excision repair enzyme that removes uracil and oxidised pyrimidines from DNA. We show that SMUG1 interacts with the pseudouridine synthase Dyskerin (DKC1) and colocalizes with DKC1 in nucleoli and Cajal bodies. As DKC1 functions in RNA processing, we tested whether SMUG1 excised modified bases in RNA and demonstrated that SMUG1 has activity on single-stranded RNA containing 5-hydroxymethyldeoxyuridine, but not pseudouridine, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…The presence of DNA-repair proteins within nucleoli is well established (Moore et al ., 2011; Antoniali et al ., 2014). In fact, several BER proteins, including SMUG1, APE1, FEN1, XRCC1, aprataxin, and PARP1/2, have been reported to accumulate within nucleoli, where they may carry out functions that differ from their “canonical” roles in DNA repair (e.g., rRNA processing; Meder et al ., 2005; Becherel et al ., 2006; Guo et al ., 2008; Vascotto et al ., 2009, 2013; Rancourt and Satoh, 2009; Jobert et al ., 2013). To the best of our knowledge, this is the first report showing that a fraction of LigI and DNA polymerase δ catalytic subunit also accumulates within nucleoli in an NPM1-dependent manner, suggesting a prominent role for NPM1 in modulating nucleolar BER accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of DNA-repair proteins within nucleoli is well established (Moore et al ., 2011; Antoniali et al ., 2014). In fact, several BER proteins, including SMUG1, APE1, FEN1, XRCC1, aprataxin, and PARP1/2, have been reported to accumulate within nucleoli, where they may carry out functions that differ from their “canonical” roles in DNA repair (e.g., rRNA processing; Meder et al ., 2005; Becherel et al ., 2006; Guo et al ., 2008; Vascotto et al ., 2009, 2013; Rancourt and Satoh, 2009; Jobert et al ., 2013). To the best of our knowledge, this is the first report showing that a fraction of LigI and DNA polymerase δ catalytic subunit also accumulates within nucleoli in an NPM1-dependent manner, suggesting a prominent role for NPM1 in modulating nucleolar BER accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar BER proteins have been suggested to exert functions related to rRNA quality control and cellular proliferation in addition to DNA repair (Guo et al ., 2008; Vascotto et al ., 2009; Jobert et al ., 2013). SMUG1 enzymatic activity, for instance, has been implicated in rRNA quality control mechanisms (Jobert et al ., 2013), whereas interfering with FEN1 nucleolar retention causes reduced survival (Guo et al ., 2008). We previously showed that impairment of nucleolar accumulation of APE1 reduces cell proliferation (Lirussi et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the major focus is on APE1, SMUG1 and PARP1, as prototypical examples [17,59,[62][63][64]. In this review, in particular, we highlight current knowledge of APE1 in controlling RNA metabolism.…”
Section: Ber Enzymes and Rna Metabolism: Unexpected Findings From Intmentioning
confidence: 99%
“…These observations demonstrate that APE1 regulates a previously unappreciated 'quality control' mechanism for nucleolar rRNA (Vascotto et al 2009). The observation that SMUG1 DNA glycosylase is also able to metabolize base-oxidized rRNA within the nucleolus (Jobert et al 2013), and D r a f t 26 that several other BER proteins are targeted to the nucleolus via NPM1 ) and may regulate rRNA transcription and/or repair (Aas et al 2003), suggest that NPM1 may be responsible for the redeployment of canonical BER proteins into a novel nucleolar rRNA quality control pathway.…”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%